I Only Want Passionate Relationships: Are You Ready for That? - Joanpere, Mar; Redondo-Sama, Gisela; Aubert, Adriana; Flecha, Ramon (Frontiers in Psychology, 2021)
Research shows the existence of a coercive dominant discourse that associates attraction with violence and influences the socialization processes of many girls and women. According to previous studies, the coercive dominant discourse constitutes a risk factor for gender violence, as men with violent attitudes and behaviours are socially presented as attractive and exciting while egalitarian and non-aggressive men are considered “not sexy”. Yet fewer evidences indicate that men acting from the New Alternative Masculinities (NAM) model overcome this double standard through verbal and non-verbal communicative acts, which tell that they do not choose women acting under the coercive dominant discourse for a relationship because they are not ‘jumping for joy’ when meeting them. Drawing from communicative life stories conducted to men and women from diverse sociocultural backgrounds and ages, this article presents how language is used in concrete heterosexual sexual-affective relationships. The analysis resulting from the fieldwork conversations focus on how NAM men’s communicative acts with women set conditions of desire. The paper shows evidence on how communicative acts of NAM empowerment incorporate ‘language of desire’, taking a clear position for egalitarian and passionate relationships. Implications for gender violence prevention are presented.